At the fringes of language: On the semiotics of noise. (January 2018) - Storch, Anne
Abstract: 'Words and alternative ways of talking […] have served as weapons against oppressive authority, vehicles for solidarity among all manner of disenfranchised peoples, and instruments of extraordinary art', Ana Cara observes (Cara, A.C. (2011). Creole talk. The poetics and politics of Argentine verbal art. In R. Baron & A.C. Cara (eds.), Creolization as cultural creativity (pp. 198–227). Jackson: University Press of Mississippi). Linguistic creativity doesn't have to be playful and amusing; it can also be about experiences of marginalization, injustice and pain. There are, consequently, different creativities and different indexicalities of creatively manipulated speech. In this article, the focus is on noisy, nonsensical, sometimes unsettling performances of linguistic creativity and on their contexts. These are only slightly different from those Cara refers to – sociolinguistic settings of inequality, based on a history of experiences of othering and subjugation among women in a small northeastern Nigerian village. The artful unmaking of words and meaning that is in the center of this contribution addresses reality in a variety of ways: it aims at evoking ideas and memories of what cannot always be seen and heard (such as spirits), of a performer's feelings of otherness. Noisy and messy communicative practice such as 'gibberish', screaming and swearing need to be seen, I argue, as performances rather than as deviations from 'proper linguistic practice'. They might digress from certain norms, but nevertheless remain interpersonal in their communicative design; they are powerful yet individual and original attempts to reach out to the other, in order to say something which might otherwise not be said. The noisy and unintelligible in language can be an attempt to retrieve what has been discarded and to put the marginal into the center. It is art that intents to remind audiences of the powers of horror, disgust, and ugliness. In practices that highlight linguistic creativity, a particularly radical way of transforming language into such abject art is to make speech (at least initially) incomprehensible, to work with obscurity, noise and disruption. The strategies used in these pieces of art are diverse: utterances are interrupted by made-up speech, and spoken text turns into sung, screamed or murmured text; noise is presented as that what belongs to the Other, and audiences are left with the task not just of listening and evaluating these performances, but also with the task of decoding them. However, noise bears in it the potential of rejection: audiences have to power to decide whether they accept, after all, the invitation to decode whatever meaning the sound of a voice may have.